2022
DOI: 10.1021/jacs.2c01809
|View full text |Cite
|
Sign up to set email alerts
|

Selective Isotope Labeling and LC-Photo-CIDNP Enable NMR Spectroscopy at Low-Nanomolar Concentration

Abstract: NMR spectroscopy is a powerful tool to investigate molecular structure and dynamics. The poor sensitivity of this technique, however, limits its ability to tackle questions requiring dilute samples. Low-concentration photochemically induced dynamic nuclear polarization (LC-photo-CIDNP) is an optically enhanced NMR technology capable of addressing the above challenge by increasing the detection limit of aromatic amino acids in solution up to 1000-fold, either in isolation or within proteins. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(64 citation statements)
references
References 80 publications
0
59
1
4
Order By: Relevance
“…472 Further, the combination of LED irradiation and selective isotope labeling, in the presence of small amounts of ascorbic acid (2 μM), recently enabled the detection of 20 nM (2.8 ng) Trp in solution. 484 In this study, LC-photo-CIDNP attenuation effects where minimized upon employing Trp-α- 13 C-β,β,β,2,4,5,6,7-d 7 , a Trp isotopologue bearing a 13 C α -1 H α pair surrounded predominantly by non-NMR-active and low-γ nuclei. 484 Given that LC-photo-CIDNP is tailored to very low concentrations of the molecule of interest (low-or submicromolar), dyes with a long triplet-state lifetime and oxygen depletion strategies are an absolute requirement.…”
Section: Chemicalmentioning
confidence: 99%
See 1 more Smart Citation
“…472 Further, the combination of LED irradiation and selective isotope labeling, in the presence of small amounts of ascorbic acid (2 μM), recently enabled the detection of 20 nM (2.8 ng) Trp in solution. 484 In this study, LC-photo-CIDNP attenuation effects where minimized upon employing Trp-α- 13 C-β,β,β,2,4,5,6,7-d 7 , a Trp isotopologue bearing a 13 C α -1 H α pair surrounded predominantly by non-NMR-active and low-γ nuclei. 484 Given that LC-photo-CIDNP is tailored to very low concentrations of the molecule of interest (low-or submicromolar), dyes with a long triplet-state lifetime and oxygen depletion strategies are an absolute requirement.…”
Section: Chemicalmentioning
confidence: 99%
“…Therefore, the potential advantage of switching magnetic field during a photo-CIDNP experiment needs to be evaluated on a case-by-case basis. , An example of the expected dependence of photo-CIDNP polarization on an applied magnetic field is provided in Figure . The simulations in this figure were carried out according to known procedures, , and employed published values of relevant parameters. …”
Section: Hyperpolarization Techniquesmentioning
confidence: 99%
“…Significant experimental and theoretical work into increasing the sensitivity of biological photo-CIDNP NMR measurements has been carried out by the group of Cavagnero in the last fifteen years. It has very recently been demonstrated that a combination of some of these setup improvements can lower the photo-CIDNP detection limit down to the low nM concentration range [14,15]. Many of these improvements can be implemented into the photo-CIDNP analysis of metabolomically relevant biofluids.…”
Section: Discussionmentioning
confidence: 99%
“…less invasive, experimental conditions and involves the instantaneous (low-power) LEDor laser light-induced generation of transient radical pairs in the presence of a small amount of a photosensitiser yielding spin-polarised molecular species [11][12][13]. In addition, photo-CIDNP is a very sensitive homo-and heteronuclear hyperpolarisation method that allows the NMR detection of analytes present in a low nanomolar concentration range provided that certain experimental requirements are met [14,15]. Traditionally, the method has been mainly employed to gauge bio-macromolecular solvent exposure in the steady state as well as in real-time owing to its ability to selectively highlight the three aromatic amino acid side-chains of tyrosine (Tyr), tryptophan (Trp), and histidine (His) as well as the aliphatic amino acid methionine (Met).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation